Knowing maintenance vulnerabilities to enhance building resilience. (2018) - Pham, Lam; Palaneeswaran, Ekambaram; Stewart, Rodney
Abstract: Information and knowledge on maintenance vulnerabilities will be significantly useful to enhance the resilience of buildings against natural disasters. An ongoing project sponsored by the Sustainable Built Environment National Research Centre in Australia aims to: (a) investigate what could be the impacts of maintenance on building resilience in extreme events such as high winds, flash floods and bush fires; (b) review current approaches, practices and policies; and (c) explore opportunities to improve resilience and values over the lifecycle of buildings. In general, the performance of buildings decreases over time and without effective maintenance, their vulnerability to extreme events will increase. What kinds of maintenance will be effective in improving the resilience of public sector building stock (such as social housing) is the key question targeted in this research. This paper presents a set of preliminary summaries from this ongoing research. The outcomes in terms of implementation strategies will be useful to building owners, governments, and insurance institutions.